TEKNIK RELAKSASI OTOT PROGRESIF UNTUK MENGURANGI STRES PASCA TRAUMA PADA PENYINTAS GEMPA PALU YANG DI UNGSIKAN DI KABUPATEN MALANG - Walda Isna Nisa (Program Studi S1 Psikologi, 2020)
The magnitude 7.7 earthquake that struck Palu on September 28, 2018, certainly had a psychological impact on those who experienced the disaster. As a result of traumatic events experienced by survivors require special psychological treatment. The impact experienced is ongoing stress followed by a traumatic experience. This study aims to reduce posttraumatic stress in survivors through progressive muscle relaxation therapy. The population in this study were 50 survivors of hammer earthquake in Malang Regency. The sampling technique used was purposive sampling with samples obtained as many as 3 people who indicated pathological symptoms. Data collection uses observation, interviews and documentation. While the interventions used in this study were Progressive Muscle Relaxation Therapy which consisted of 3 sessions in 1 meeting for 60 minutes and held 4 meetings a week. Session 1 identified the perceived muscle tension, session 2 carried out progressive muscle relaxation therapy, and session 3 distinguishes and compares what is felt when muscles are stretched and relaxed. This progressive muscle relaxation technique aims to reduce stress due to traumatic experiences. The results showed that this progressive muscle relaxation technique can reduce stress resulting in muscle tension such as muscle cramps, headaches, anxiety, insomnia and excessive stress because of the trauma experienced by the three survivors. Progressive muscle relaxation performed has been shown to reduce the physiological and emotional components of stress experienced by the three survivors so that the three survivors have decreased stress.